ECO-FRIENDLY MACHINING OF SUPER DUPLEX STAINLESS STEEL (UNS S32760) UNDER NITROGEN GAS COOLED AND VEGETABLE OIL BASED MQL SYSTEM - M.Saravanakumar, P. Tamilselvam , M.Subramanian, C.Somu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Super duplex stainless steel (SDSS) is most extensively used in offshore and marine applications because of their excellent corrosive resistance and good mechanical properties. Although, due to high levels of various alloying elements machinability of super duplex stainless steel is very poor. In this present work experimental investigation of turning of super duplex stainless steel UNS S32760 in CNC lathe machine (Make: Jyoti DX 200) with (Al,Ti)N coated carbide tools under various cutting conditions like dry, nitrogen gas cooled environment and MQL machining in vegetable oil (Acculube LB 2000) by using Taguchi technique. The experiments were performed at three different cutting speeds (75, 100 and 125 m/min) with three different feed rates (0.05, 0.15 and 0.25 mm/rev) and a constant cutting depth (1 mm). Using signal to noise ratio and analysis of variance, the cutting parameters are optimized. The effects of cutting speed and feed rate on surface roughness, cutting temperature and tool wear were studied. The result shows that the feed rate is the more significant parameter that influencing the surface roughness. The cutting speed was identified as the more significant parameter influencing the cutting temperature and tool wear. The results show that MQL machining has better performance reduction in surface roughness, cutting temperature and tool wear when compared to Nitrogen gas cooled and dry machining